Sampah Dalam Kacamata Media Online - Rr. Pramesthi Ratnaningtyas (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
The aim of this research is to explain how Tribunjogja.com constructs and frames the issue of trash (Jogja Darurat Sampah) in the period of March to April 2019. During the time, news articles were narrowed based on the TPST Piyungan tag (#TPSTPiyungan) until 43 online news stories were obtained on 11 different dates. This study uses a qualitative and constructionistparadigm approach. Agenda Setting theory is employed in conjunction with Entman's framing analysis which has four elements: defining the problem, diagnosing the cause, making moral judgments, and treatment recommendations. The integration of the theories and analysis aims to see the tendency of Tribunjogja.com in responding to problems (of trash) in the society. The results showed that the news revealed the facts of social and economic problems that occur in the community related to trash problems. The closure of TPST Piyungan (integrated landfills) conducted by residents departs from poor trash management. The domino effect is the over accumulation of garbage in temporary landfills (TPS) and depots, even scattering on the road. Economically, this problem disrupts the income of people who have jobs collecting trash from people's homes. This problem is closely related to the economical, social, and sanitation aspects of the wider community. Trash becomes a time bomb that demands government policies that considering the social aspects of local residents of TPST Piyungan, and the wider society. Penelitian ini bertujuan untuk menjelaskan bagaimana Tribunjogja.com mengonstruksi dan membingkai isu sampah (Jogja Darurat Sampah) pada periode Maret hingga April 2019. Dalam kurun waktu tersebut, artikel berita dipersempit berdasarkan tag TPST Piyungan hingga didapatkan 43 berita daring pada 11 tanggal yang berbeda. Dengan demikian, digunakan pendekatan kualitatif dan paradigma konstruksionis. Teori agenda setting digunakan bersama analisis framing Entman yang memiliki elemen define problems, diagnose causes, make moral judgement, dan treatment recommendation. Penggabungan teori dan analisis tersebut untuk melihat kecenderungan pemberitaan Tribunjogja.com dalam merespon permasalahan di lapangan. Hasil penelitian menunjukkan bahwa berita cenderung memunculkan aspek sosial dan ekonomi. Mengingat penutupan atau blokade TPST Piyungan yang dilakukan warga setempat berangkat dari pengelolaan TPST yang tidak baik. Dampak penutupan itu membuat sampah menggunung di TPS dan depo-depo, bahkan berceceran sampai di jalan. Secara ekonomi, terlihat tertutupnya pendapatan warga yang memiliki pekerjaan jasa pengambilan sampah dari rumah-rumah penduduk. Hal tersebut terkait dengan hajat hidup dan kesehatan masyarakat luas. Sampah menjadi bom waktu yang menuntut kebijakan pemerintah yang tidak menanggalkan aspek sosial bagi warga setempat TPST Piyungan pada khususnya, dan masyarakat luas pada umumnya.